Aromatic compounds lead to increased abundance of antibiotic resistance genes in wastewater treatment bioreactors. (1st December 2019) - Xia, Juntao; Sun, Haohao; Zhang, Xu-xiang; Zhang, Tong; Ren, Hongqiang; Ye, Lin
Abstract: Various aromatic compounds in wastewater, especially industrial wastewater, are treated by biological processes in bioreactors which are regarded as hotspots and reservoirs of antibiotic resistance genes (ARGs). Yet, little is known about the relationship between the aromatic compound degradation process and antibiotic resistance. Here, we report on the co-occurrence of ARGs and aromatic degradation genes (ADGs) in bacteria in bioreactors. We confirmed this by bioreactor experiments and bioinformatics analysis of over 10, 000 publicly available bacterial genomes. We observed a significant enrichment of ARGs in bioreactors treating wastewater that contained p -aminophenol and p -nitrophenol. The potential hosts harboring ARGs and ADGs were mainly Pseudomonas, Leucobacter, Xanthobacter, Acinetobacter, and Burkholderiaceae. Genome analysis revealed that 67.6% of the publicly available bacterial genomes harboring ADGs also harbor ARGs. Over 80% of Burkholderiales, Xanthomonales, Enterobacteriaceae, Acinetobacter, Pseudomonas, and Nocardiaceae genomes harbor both ARGs and ADGs, which strongly suggests the co-occurrence of these genes. Furthermore, bacteria carrying ADGs harbored more than twice the number of ARGs than bacteria only carrying ARGs. Network analysis suggested that multidrug, beta-lactam, aminoglycoside, macrolide-lincosamide-streptogramin, and polymyxin resistance genes are the major ARGs associated with ADGs. Taken together, the presented findings improve the understanding of ARG prevalence in biological wastewater treatment plants, and highlight the potential risk of the effect of regular aromatic compounds on the selection and spread of ARGs. Graphical abstract: Image 1 Highlights: ARGs were enriched in bioreactors treating wastewater containing aromatic compounds. Co-occurrence of ARGs and aromatic degradation genes was observed in bacteria. Bacteria carrying aromatic degradation genes harbor more ARGs than other bacteria. The effects of aromatic compounds on selection of ARGs are worthy of attention.